THE RELATIONSHIP BETWEEN PARENTING STYLE AND DEPRESSION AMONG ADOLESCENTS - Olutunde, Olatunji Samuel (IJRDO- Journal of Educational Research, 2017)
This study examines the relationship between parenting style and depression among adolescents. Parenting style was grouped into three categories viz; Authoritarian, Permissive and Authoritative. Three non-directional hypotheses were formulated to answer the research questions raised in this study. The first hypothesis states that there will be a significant relationship between authoritarian parenting style and depression among adolescents. The second hypothesis states that there will be a significant relationship between permissive parenting style and depression among adolescents. The third hypothesis states that there will be a significant relationship between authoritative parenting style and depression among adolescents. A sample size of 180 participants comprising 90 male and 90 female between ages 12 – 18 years drawn from SS2 students of five Secondary Schools in lkare-Akoko,Ondo State, Nigeria respectively responded to Self – rating Depression Scale [SDS] and Parental Care Scale [PCS]. Participants’ scores were subjected to analysis with Hierarchical Multiple Regression analysis and result shows that; Authoritarian parenting style has a significant relationship with depression among adolescents. Permissive parenting style also has a significant relationship with depression among adolescents. Authoritative parenting style has a significant relationship with depression among adolescents. Based on these findings, the present study has demonstrated that a significant relationship actually exist between parenting style and depression among adolescents. The present study recommended that adolescents should be given the necessary assistance so that they will be able to cope with the stressors that accompany living in either of the three parenting style.